Allogeneic human umbilical cord-derived mesenchymal stem/stromal cells for chronic obstructive pulmonary disease (COPD): study protocol for a matched case–control, phase I/II trial. Issue 5 (13th May 2021) - Hoang, Duc M; Nguyen, Kien T; Nguyen, Anh H; Nguyen, Bach N; Nguyen, Liem Thanh
Abstract : Introduction: The global prevalence of chronic obstructive pulmonary disease (COPD) is increasing, and it has become a major public health burden worldwide, including in Vietnam. A large body of preclinical and clinical studies supports the safety of mesenchymal stem/stromal cells (MSCs) in the treatment of lung injury, including COPD. The aim of this trial is to investigate the safety and potential therapeutic efficacy of allogeneic administration of umbilical cord-derived MSCs (UC-MSCs) as a supplementary intervention in combination with standard COPD medication treatments in patients with moderate-to-severe COPD based on the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2019 and Vietnam Ministry of Health's guidelines. Methods and analysis: This matched case–control phase I/II trial is conducted at Vinmec Times City International Hospital, Hanoi, Vietnam between June 2020 and December 2021. In this study, 40 patients will be enrolled and assigned into two age-matched, gender-matched and COPD condition-matched groups, including a UC-MSC group and a control group. Both groups will receive standard COPD medication treatment based on the GOLD 2019 guidelines and the Vietnam Ministry of Health protocol. The UC-MSC group will receive two doses of thawed UC-MSC product with an intervention interval of 3 months. The primary outcome measures will include the incidence of prespecified administration-associated adverse events and serious adverse events. The efficacy will be evaluated based on the absolute changes in the number of admissions, arterial blood gas analysis, lung function and lung fibrosis via CT scan and chest X-ray. The clinical evaluation will be conducted at baseline and 3, 6 and 12 months postintervention. Ethics and dissemination: Ethical approval was secured from the Ethical Committee of Vinmec International Hospital (number:166/2019/QĐ-VMEC) and Vietnam Ministry of Health (number:2002/QĐ-BYT). The results will be reported to trial collaborators, publication in peer-reviewed academic journals. Trial registration number: NCT04433104 .